Impact of Ophthalmic Viscosurgical Devices in Cataract Surgery. (20th October 2020) - Malvankar-Mehta, Monali S.; Fu, Angel; Subramanian, Yasoda; Hutnik, Cindy
Abstract : Background . Ophthalmic viscoelastic devices (OVDs) used during small-incision cataract surgery have numerous advantages. However, OVDs have longer retention time in an eye after surgery resulting in intraocular pressure (IOP) spikes. The purpose of this study is to analyze and quantify the effect of various OVDs on both IOP and best corrected visual acuity (BCVA) by systematically reviewing the literature and performing meta-analysis. Methods . Numerous databases from January 1, 1985, to present were systematically searched. Thirty-six (3893 subjects) of 3313 studies identified were included for analysis. Standardized mean difference (SMD) was computed, and meta-analysis was performed. Results . A total of 3313 records were retrieved including 1114 from database search and 2199 from grey literature search. Significant increase in postoperative IOP in 1-day follow-up with Healon (SMD = 0.37, CI: [0.07, 0.67]), Viscoat (SMD = 0.29, CI: [0.13, 0.45]), Provisc (SMD = 0.46, CI: [0.17, 0.76]), and Soft Shell (SMD = 0.58, CI: [0.30, 0.86]) was computed. On the other hand, results implied a nonsignificant increase in postoperative IOP with Healon GV (SMD = 0.07, CI: [−0.28, 0.41]), Healon5 (SMD = 0.15, CI: [−0.33, 0.64]), 2% HPMC (SMD = 0.32, CI: [−0.0, 0.64]), and OcuCoat (SMD = 0.26, CI: [−0.37, 0.9]). Additionally, a nonsignificant reduction in postoperative IOP was inferred with Viscoat + Provisc (SMD = −0.28, CI: [−2.23, 1.68]). Conclusion . Improvement in IOP was shown with Viscoat + Provisc. Additionally, IOP nonsignificant upsurge was observed with Healon GV, Healon5, 2% HPMC, and OcuCoat compared to significant upsurge with Healon, Viscoat, and Soft Shell.